Holocene sedimentary of the Pearl River Delta in South China: OSL and radiocarbon dating of cores from Zhuhai - Lin, Penghui; Xu, Xiaolin; Yan, Chaoyang; Luo, Lan; Abbas, Mahmoud; Lai, Zhongping (Frontiers in Marine Science, 2022)
Sedimentary archives of coastal deltas provide a window for investigating interactions between deltaic evolution and natural drivers (including sea-level change, hydrodynamic and palaeomorphology), as well as human activities. Previous studies revealed that the Holocene sedimentation process of the Pearl River Delta (PRD) in South China, one of the world’s largest coastal deltas, was well recorded in its estuarine sediments. However, the limited chronology data hinders the detailed interpretation of these records. The current study presents quartz optically stimulated luminescence (OSL) and radiocarbon (14C) dating for two cores (P1-1, with a depth of 79 m and P3-2, with a depth of 60 m) from the Xijiang estuary in Zhuhai, and the reconstruction of the Holocene sedimentary history. The thirteen OSL ages of core P1-1 ranges from 10.4 to 0.16 ka. Core P3-2 spans from 10.7 to 0.3 ka with eight quartz OSL ages and eight 14C ages. OSL and 14C data shows good consistency above 26 m (1.4 – 0.3 ka), but with discrepancy at depths of 28 – 54 m where 14C ages (8.1–10.7 ka) are generally older than quartz OSL ages. The Holocene sedimentary history of the southern PRD was reconstructed using the obtained chronostratigraphy, together with analyses of lithology characteristics and sediment accumulation rates. Three-phased sedimentation occurred: (1) fast accumulation rates of 7.39–7.47 m/ka between 10.7 and 7.5 ka as a result of rapid marine transgression, (2) followed by significantly decreasing rates of 0.70–2.25 m/ka from 7.5 to 2.5 ka in response to reduced sediment supply and tidal process, and (3) rapid sedimentation rate of 8.89–9.09 m/ka since 2.5 ka associated with intensive human activities and weakening tidal hydrodynamic. This sedimentary model is also evident in many other Asian deltas.